Twitter as an Information Dissemination Source for Delivering Crisis Information during the Outbreak of the COVID-19 Pandemic - Altayar, Mohammed (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
This study aims to investigate the use of Twitter by Saudi government agencies as an information dissemination source to communicate COVID-19-related information. A total of 8,718 tweets from 33 government agencies were collected during a nine-month period from 1 January to 30 September 2020. The results show that Twitter played a dominant role in the crisis communication process. In addition, providing instructions and adjusting information, as well as management reputation, was a basic strategy to respond to the COVID-19 crisis. Furthermore, communication in terms of topics, actors, style, tones and quantity has changed during different phases of the crisis. The study argues that a centralized and highly organized government structure is particularly important in driving an information and communication strategy to tackle the pandemic, and it helps deliver messages with a common identity that promotes extensive public and government interaction.